2018
DOI: 10.1111/add.14474
|View full text |Cite
|
Sign up to set email alerts
|

Illicit fentanyls in the opioid street market: desired or imposed?

Abstract: Background-Illicitly manufactured fentanyl and its analogues are appearing in countries throughout the world, often disguised as heroin or counterfeit prescription pills, with resulting high overdose mortality. Possible explanations for this phenomenon include reduced costs and risks to heroin suppliers, heroin shortages, user preferences for a strong, fast-acting opioid and the emergence of Dark Web cryptomarkets. This paper addresses these potential causes and asks three questions: (1) can users identify fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 45 publications
2
82
0
Order By: Relevance
“…The high level of potency also helps to explain their lethality. According to law enforcement sources, fentanyl compounds are increasingly packaged and sold as “heroin” by drug dealers . Prices of the adulterated drug may be cheaper than heroin itself and the increased potency may even be a selling point, despite the clear risk for overdose .…”
Section: Vector Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high level of potency also helps to explain their lethality. According to law enforcement sources, fentanyl compounds are increasingly packaged and sold as “heroin” by drug dealers . Prices of the adulterated drug may be cheaper than heroin itself and the increased potency may even be a selling point, despite the clear risk for overdose .…”
Section: Vector Factorsmentioning
confidence: 99%
“…A key question is how much do people who use drugs actively seek fentanyl versus how much is surreptiously added to the drug supply? While unintentional ingestion is certainly common, it appears that fentanyl is actively sought by some individuals who use drugs, and the high potency, as indicated by overdoses, may encourage the use of particular drug supplies . A study in New Hampshire interviewed people who use opioids about their practices and attitudes toward heroin versus fentanyl found that 25% specifically sought fentanyl or heroin laced with fentanyl over other opioids .…”
Section: Vector Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study limitations include sampling from a single city, which limits generalizability to other locations, and a longer self-reported use period than drug detection periods. There was also no direct assessment of known fentanyl use as distinct from other opioid pain medication [30] for this secondary data analysis. Study strengths include longitudinal comparisons of both self-reported and mass-spectrometry toxicology-confirmed substance use, a focus on stimulant use, and a focus on women.…”
Section: Discussionmentioning
confidence: 99%
“…Or rather, were the observed shifts in drug supply a response to existing domestic demand-side forces? Select examinations have sought to explore this question, including a 'three-wave' characterization of recent opioid supply, yet findings seem to primarily emphasize evolutionary developments in international illicit opioid production and distribution chains as the main drivers behind the opioid crisis unfolding in North America [21,22]. Substantial evidence supports the former perspective, namely that the recent 'wave' of toxic illicit opioid supply has emerged as an interrelated consequence within preexisting opioid demand and supply dynamics.…”
Section: Main Textmentioning
confidence: 99%